Analysis of changes in electrogenesis in schizoprenia using computer electroencephalography - B. A. Lobasyuk; L. B. Bartsevich (Kazimierz Wielki University, 2020)
Rationale. Psychiatrists do not have objective methods for identifying the brain disorders responsible for mental illness, which prevents timely diagnosis. Therefore, the search for markers of this disease, primarily related to CNS activity, is very relevant. The purpose. A comparative study; by using periodometric analysis of EEG indicators, interhemispheric asymmetry of EEG rhythm amplitudes, and by using multiple regression analysis to identify connections-relations between EEG amplitude and frequency rhythms of different leads in healthy people and schizophrenic patients. Material and Methods. EEG recording was performed in a state of quiet wake with closed eyes on the Neuron-Spectrum-2 electroencephalograph. The analysis was performed using periodometric analysis. The differences of the indicators were monitored using the calculation of the coefficients of concordance (CCs). Connections-relations between indicators were investigated using multiple regression analysis. Own research. In patients with schizophrenia compared with healthy people, there was detected a decrease in the amplitudes of rhythms of EEG, an increase in the duration indices in the delta and theta ranges and a decrease in the duration indices of the alpha and beta rhythms. In patients with schizophrenia, there was a decrease in negativity and an inversion of functional interhemispheric asymmetry (FIHA) to positivity in the delta, theta, and alpha ranges and an increase of (FIHA) positivity in low-frequency and high-frequency EEG beta rhythms. Multiple regression and correlation analysis of the rhythm amplitudes interactions revealed that in the delta and theta ranges in the main group the number of regression coefficients was less than in the control group and in alpha, beta-LF and beta-HF - more than in control group. Conclusions. 1. The obtained results indicated the activation of the right hemisphere in comparison with the left in patients with schizophrenia, possibly due to a decrease in the activating effect of the reticular formation of the brain stem. 2. It has been suggested that these changes in the aggregate are the neurophysiological basis of disorders of higher nervous (mental) activity in patients with schizophrenia